Private Contracting and the Hidden Cost of Burden Shifting: The Case of Prison Food. Issue 4 (7th August 2020) - Zullo, Roland
ABSTRACT: Burden shifting is an increase in risk or responsibility for coworkers or clients caused by inadequate agent performance. In this study, focus group testimony from corrections officers is used to elucidate burden shifting in the prison context. In 2013, Michigan privatized prison food service management statewide, which set in motion a series of negative reciprocating effects that increased risks for officers, inmates, and contract employees; intensified gang control of kitchen areas; and shifted a share of food operations duties to the officers stationed in the chow hall area. The findings have implications for agency theory and prison administrative practice.